2020
DOI: 10.1515/hmbci-2020-0033
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin D deficiency and prevalence of metabolic syndrome in female population: a systematic review

Abstract: BackgroundThe increasing prevalence of metabolic syndrome (MS) especially in female population, has become a major problem in health care systems. In this regards, it is necessary to identify the risk factors. Vitamin D deficiency is now proposed as one of the possible risk factors for metabolic syndrome, we investigated the relationship between vitamin D status and MS in female.MethodsWe searched observational studies with keywords Vitamin D, metabolic syndrome, metabolic syndrome X, insulin-resistance syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A follow-up study conducted among healthy adolescent girls in Iran reported that there were significant reductions in DBP, WC, and serum FBG, TC, and LDL-C after the 9-week vitamin D supplementation, but no significant effects were observed on BMI, SBP, serum HDL-C, or TG [ 52 ]. Moreover, a recent meta-analysis including nine cross-sectional studies indicated that abdominal obesity, high BP, high TG, and reduced HDL-C were statistically associated with vitamin D status in the female population [ 53 ]. In our study, elevated WC and TG and reduced HDL-C were associated with insufficient vitamin D among women of childbearing age.…”
Section: Discussionmentioning
confidence: 99%
“…A follow-up study conducted among healthy adolescent girls in Iran reported that there were significant reductions in DBP, WC, and serum FBG, TC, and LDL-C after the 9-week vitamin D supplementation, but no significant effects were observed on BMI, SBP, serum HDL-C, or TG [ 52 ]. Moreover, a recent meta-analysis including nine cross-sectional studies indicated that abdominal obesity, high BP, high TG, and reduced HDL-C were statistically associated with vitamin D status in the female population [ 53 ]. In our study, elevated WC and TG and reduced HDL-C were associated with insufficient vitamin D among women of childbearing age.…”
Section: Discussionmentioning
confidence: 99%
“… 88 In addition, the prevalence of abdominal obesity, high BP, hypertriglyceridemia, and high-density lipoprotein (HDL) deficiency was higher in vitamin D-deficient women. 88 91 In another meta-analysis including 28 studies, a higher serum 25(OH)D3 levels were associated with a 51% lower risk of MS, 55% reduction in diabetes, and 33% lower risk of cardiovascular disease. 92 In a recent systematic review and meta-analyses of a total of 23 observational studies (19 cross-sectional studies and four cohort studies), Lee and Kim 93 showed that 25 nmol/L (10 ng/mL) increment in the serum 25(OH)D3 concentration was associated with 20% and 15% lower risks of MS in cross-sectional studies and cohort studies, respectively.…”
Section: Vitamin D Deficiency and Metabolic Syndromementioning
confidence: 99%
“…25-hydroxyvitamin D (25(OH)D) is a commonly used biomarker for vitamin D status [3]. Accumulating studies have shown that low concentrations of 25(OH)D are associated with numerous health conditions, including bone health [4], glucose homeostasis [5], development of hypertension and cardiovascular disease [6], cancer-related mortality and progression [7], depression [8], inflammation [9], multiple sclerosis [10], and metabolic syndrome [11]. Based on clinical 2 of 15 recommendations, individuals with serum 25(OH)D levels ≤ 20 ng/mL and 21-29 ng/mL are defined as having vitamin D deficiency and insufficiency, respectively [3,12].…”
Section: Introductionmentioning
confidence: 99%